Effectiveness of the Healthy e-Elderly People Intervention (HEPI) mobile application for the reduction of physical health effects caused by smartphone usage among elderly individuals in Thailand - Wachiraporn Wilaiwan; Wattasit Siriwong (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - The study aimed to evaluate the effectiveness of the Healthy e-Elderly People Intervention (HEPI) mobile application in reducing the physical health effects caused by smartphone usage. Design/methodology/approach - This randomized controlled trial involved elderly volunteers residing in different regions of Thailand and using smartphones. The samples included 33 participants in each control and intervention group. The intervention group received the HEPI application with reminder messages, while the control group received the HEPI application without reminder messages. Assessments were conducted at baseline, follow-up 1 (four weeks after the last reminder messages) and follow-up 2 (12 weeks after the last reminder messages). Data analyses (i.e descriptive statistics, independent sample t-tests and repeated-measures analysis of variance) were used to obtain the overall mean change difference between the intervention and control groups at different time points (per-protocol analysis). The priorities of physical health risk were assessed using Health Risk Matrix. Findings - The HEPI mobile application significantly improved knowledge, attitudes and practice scores in both the HEPI with and without reminder messages. The mean physical health risk score in both control and intervention groups was radically decreased from baseline to follow-up 1; lower physical health scores suggested lower health risk. Originality/value - Increased duration of smartphone usage by elderly individuals in Thailand may result in a risk of developing several serious health conditions. The HEPI application with reminder messages could be used as a tool to benefit smartphone users and would further benefit from a booster after four weeks of intervention.